CREATING A WELCOMING CLASSROOM ENVIRONMENT FOR YOUNG LEARNERS AT MERLION SCHOOL, SURABAYA - Hertiki Hertiki (Magister Scientiae, 2017)
One of the biggest obstacles facing teachers of young learners is classroom management. Classroom management is needed to control students’ behavior, movement and interaction during a lesson in class. A good teacher is someone who is kind, patience, and loves the students. Creating a caring classroom environment for young learners is not an easy task for any teacher. Young learners are full of energy and each child is totally different. Maintaining discipline and setting up activities are needed in creating a good atmosphere for the children. Classroom environment for young learners should be fun and also create a safe learning environment where students feel comfortable. This paper briefly explains about classroom management at Merlion School (MS) Surabaya, Indonesia. Here, the teacher uses some classroom management strategies to facilitate a conducive environment in class such as: setting up the classroom rules, the proper seating arrangement, giving rewards, creating students’ birthday cards, providing book corner, assigning weekly leaders, and providing the cubby holes for students.